Scalable and Fast Electrical Modeling Method for Bonding-Wire Memory Packages - Dongryul Park; Seonghi Lee; Seunghun Ryu; Hyunwoo Kim; Duksoo Kim; Hyunsik Kim; Jongwook Kim; Seungyoung Ahn (IEEE Access)
With the increasing demand for high-speed and cost-effective memory solutions, bonding wire (BW)-based memory packages are adopted in various applications. Designing BW based memory packages requires numerous changes in design parameters of multiple components. However, using traditional 3D electromagnetic (EM) simulations to accommodate these changes results in long computation times and high design cost. To address this limitation, a method is needed that allows rapid evaluation of the entire memory package’s performance, regardless of design parameter changes. Thus, we propose a scalable and fast modeling method for the full memory package. The proposed method provides modeling methods for each package component, including BW, pad, transmission line (TL), via, and ball. The BW, via, and ball modeling rely solely on simple formulas, enabling rapid computation. Similarly, pad and TL modeling leverages 2D EM simulations with low computational overhead and employs an S-parameter extension method to achieve fast modeling even in multi-conductor scenarios. To accelerate the modeling process, matrix reduction and parallel processing are utilized. Finally, the in-house code connects the component models, creating the full memory package. The proposed method’s consistency, scalability, and fast computation times are validated through comparisons with 3D EM simulations. Validation is performed in both the frequency domain, covering a wide bandwidth up to 40 GHz, and the time domain. The results demonstrate that the proposed modeling technique is scalable, accurate, and reduces computation time by 99% compared to 3D EM simulations while maintaining consistency.